Parents’ Participation in Extracurricular Programmes at Primary Schools in Surakarta - Ambawani, Cettra Shandilia Latunusa; Haryanto, Sigit; Yunianto, Aan; Kusuma, Thitha Meista Mulya; Fuadi, Jalal (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Participation plays an important role in the success of school programs. However, in reality, there are still obstacles to increasing parental participation, so a strategy is needed in an effort to optimize parental participation in school programs. The objectives of the study are (1) to describe parents’ participation in school programs; (2) to describe school strategies to optimize parents’ participation in school programs; and (3) to describe the outcomes achieved when a school strategy was implemented to maximize parent participation in State Elementary School Sayangan. The methodology utilized is a subjective way to deal with the plan of contextual investigations. The research results show that (1) parent and teacher communication through WAG and written invitations; (2) an intense approach strategy or open communication by maximizing the role of IOM for each class through regular meetings to develop programs; and (3) IOM’s involvement can increase the success of the adiwiyata competition program, alert bazaar, steady front group, and work title festival during learning. The conclusion of the research is that communication is very important in student activities at school and that success will be achieved with good cooperation between teachers, students, and parents.